2002
DOI: 10.1002/pon.569
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in childhood cancer survivors

Abstract: The successful treatment for children with cancer has greatly increased the survival rates for these young people compared to children diagnosed with cancer 30 years ago. These new medical realities direct attention to the psychosocial consequences of successful treatment and subsequent survival. In this paper, quality of life in 176 childhood cancer survivors (age 16-28) is assessed using a survey instrument designed for cancer survivors. In addition, the instrument is evaluated for its utility with this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
165
2
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(193 citation statements)
references
References 36 publications
17
165
2
9
Order By: Relevance
“…95 Research on positive outcomes among cancer survivors suggests that many view their treatment as an event that led to reevaluation of their life priorities, greater appreciation of relationships, greater sensitivity to needs of others, posttraumatic growth related to perceived threat to life, improved coping ability, and greater overall life satisfaction. 74,40,96 These preliminary findings are encouraging and suggest a high level of psychological resilience among many cancer survivors. At the same time, cancer survivors' hopefulness may be tempered by uncertainty, and, for some survivors, it may be difficult to find meaning and personal growth in their cancer experience.…”
Section: Group 3: Patients With Subsyndromal Symptoms and Existentialmentioning
confidence: 66%
See 2 more Smart Citations
“…95 Research on positive outcomes among cancer survivors suggests that many view their treatment as an event that led to reevaluation of their life priorities, greater appreciation of relationships, greater sensitivity to needs of others, posttraumatic growth related to perceived threat to life, improved coping ability, and greater overall life satisfaction. 74,40,96 These preliminary findings are encouraging and suggest a high level of psychological resilience among many cancer survivors. At the same time, cancer survivors' hopefulness may be tempered by uncertainty, and, for some survivors, it may be difficult to find meaning and personal growth in their cancer experience.…”
Section: Group 3: Patients With Subsyndromal Symptoms and Existentialmentioning
confidence: 66%
“…23 Long-term survivors of pediatric leukemia, Hodgkin disease, and non-Hodgkin lymphoma were more likely to report symptoms of depression and somatic distress than their sibling controls, and having high dose chemotherapy contributed to the risk of developing these symptoms. 74 Elevated levels of distress were also reported by long-term survivors of testicular cancer whose anxiety scores-as captured by HADS-were reliably higher than those among males in the general population. 56 Psychological distress indicative of psychiatric disorder was reported by 31% of physically healthy BMT and leukemia survivors 5 years after termination of active treatment.…”
Section: Group 2: Patients With Psychiatric And/or Psychological Sequmentioning
confidence: 94%
See 1 more Smart Citation
“…siblings) (Stam et al, 2006;Reinfjell et al, 2009;Zeltzer et al, 2009). However, most studies found that on the whole, survivors of childhood cancer fare the same or have a good QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and function well psychologically (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008). Yet, only a few studies had reported results by both parent proxy and adolescent self-report, compared with controls.…”
Section: Quality Of Lifementioning
confidence: 99%
“…While a number of studies have reported adverse outcomes (Grant et al, 2006;Speechley et al, 2006;Stam et al, 2006;Reinfjell et al, 2009;Gurney et al, 2009;Nathan et al, 2009;Hudson et al, 2003;Mulhern et al, 2004;Oeffinger et al, 2008), others have concluded that QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and psychosocial adjustment (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008) are satisfactory for the majority of long-term childhood cancer survivors. Finally, a few studies have found that the prevalence of depression in survivors of childhood cancer equal that of healthy controls (Gray et al, 1992;Zebrack and Zeltzer, 2003).…”
Section: Introductionmentioning
confidence: 99%